Association between Smoking and Perceived Social Support among Tehranian Adults: Tehran Lipid and Glucose Study - Sara Jalali-Farahani; Parisa Amiri; Ahmad Khalili-Chelik; Mehrdad Karimi; Fereidoun Azizi (Hamadan University of Medical Sciences, 2018)
Background and Objective: Smoking has various socio-economic consequences and is related with social support. This study was conducted with the aim of investigating the association between smoking and social support from families, friends, and significant others in adults. Materials and Methods: This cross sectional study was conducted between 2014 and 2016 in the framework of Tehran Lipid and Glucose Study (TLGS) on 1068 adults. Perceived social support was assessed, using Multidimensional Scale of Perceived Social Support (MSPSS). The data were analyzed by SPSS 20, using Chi-square and Mann Whitney tests as well as and binary regression method. Results: The mean age of the participants was 49.9±15.0 years and 59.4% of them were female; 0.9.2% of the participants were smokers and most smokers were male (76.5%). Non-smokers reported higher scores in perceived social support from family (p=0.040) and significant others (p=0.036) compared to smokers. After moderating the intervening factors, smokers were more likely to report low perceived social support from family 2.04 times more than their non-smoker counterparts (95%CI: 1.11-3.73; p<0.05). Conclusion: Smokers are more likely to report low perceived social support from family compared to non-smokers.